2020
DOI: 10.1371/journal.pone.0238398
|View full text |Cite
|
Sign up to set email alerts
|

Transversal sero-epidemiological study of Bordetella pertussis in Tehran, Iran

Abstract: Objectives Pertussis remains endemic despite high vaccine coverage in infants and toddlers. Pertussis vaccines confer protection but immunity wanes overtime and boosters are needed in a lifetime. Iran, eligible for the Expanded Program on Immunization that includes the primary immunization, implemented two additional booster doses using a whole-cell vaccine (wPV) at 18 months-old and about 6 years-old. Duration of protection induced by the wPVs currently in use and their impact as preschool booster are not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Only 4 infants were late in starting the vaccination program among the 199 participating infants, and > 90% of those infants who were vaccinated complied with the national vaccination schedule in this study. Compliance with vaccination schedule was also found to be very good among vaccinated children 3–15 years old in Tehran, confirming our data [ 10 ]. Timeliness may nevertheless vary throughout the country as high incidence of delayed vaccination was reported in the outskirt of Iran’s big cities [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Only 4 infants were late in starting the vaccination program among the 199 participating infants, and > 90% of those infants who were vaccinated complied with the national vaccination schedule in this study. Compliance with vaccination schedule was also found to be very good among vaccinated children 3–15 years old in Tehran, confirming our data [ 10 ]. Timeliness may nevertheless vary throughout the country as high incidence of delayed vaccination was reported in the outskirt of Iran’s big cities [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…This relationship with infant and age distribution of primary case contacts was recently shown to be similar in HIC where aPVs are used [ 24 ]. The important rate of pertussis infection among contact cases observed herein highlights the underreporting among older children and adults and are in line with studies evidencing substantial circulation of pertussis among Iranian children and adolescents [ 10 , 25 ]. In addition, although all positive children presented symptoms, more than 30% of older individuals did not recall having or did not have cough at any time during the study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent serosurvey study that was published after the review search period assessed children and adolescents aged 3-15 years in Tehran between December 2016 and February 2017. The seroprevalence of anti-PT IgG showed that B. pertussis was circulating, despite high coverage of childhood pertussis vaccination and the pre-school booster [61]. Among serum samples from 1010 children and adolescents, the seropositivity rate (PT IgG [ 40 IU/ml) was significantly higher among children who received their first booster dose 5-6 years previous to the study compared with those who had received it within 1-2 years (30.4% versus 2.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In children who had received the second booster dose, seropositivity rates in children receiving it within 1 years and 1-2 years were 27.7% and 32.5%, respectively, and rates were significantly lower in children receiving it within 2-3 years (11.1%). The authors suggest that vaccine-acquired immunity after the first booster dose at 18 months had waned within about 2 years and that a second booster dose in children aged 5-6 years improves longer term antibody persistence [61].…”
Section: Discussionmentioning
confidence: 99%